Optimalisasi Peran Bank Syariah dalam Mengembangkan Industri Halal di Indonesia Melalui Sinergi Kelembagaan - Sri Apriyanti Husain (JES (Jurnal Ekonomi Syariah), 2021)
Abstract: The halal industry in Indonesia is expected to grow faster than in other countries. However, this can be achieved if it can optimize the financial sectors, one of which is Islamic banks. Islamic banks have an essential role in developing the halal industry. This is also, of course, inseparable from Indonesia’s demographic bonus as a country with the largest Muslim population in the world. The Researcher used qualitative descriptive research as a research method. The Researcher conducted an exploratory study on optimizing the role of Islamic banks in developing the halal industry in Indonesia. Islamic banks must optimize their function through institutional synergy. Institutional synergies that Islamic banks must carry out to maximize their role in developing the halal industry in Indonesia are: First, institutional synergy with the government. The forms of institutional synergy carried out by the government Islamic banks are (1) identification and mapping of areas for the halal tourism sector; (2) support for strengthening regulations, standardization, and supervision processes for halal products. Second, the institutional synergy of Islamic banks with halal industry players. The form of institutional synergy with Islamic banks with the halal industry can be done by (1) identification and development of industrial models; (2) support for strengthening and providing outlets and market access; (3) provision of financing funds; (4) education and assistance. And the third is the synergy of Islamic banks with educational institutions by including halal industry awareness in educational institutions.